Kriya Keramik Modern Dengan Teknik Putar - Muhamad Asri Romadhan; Jupriani Jupriani (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this creation is to 1) create modern ceramic crafts as an effort to develop ceramic craft designs in West Sumatra, 2) make ceramic crafts a source of income for the author, 3) as a requirement for the author to complete undergraduate studies at Padang State University. The method for creating works uses the method according to Bandem (2001:10), the creation method consists of five stages, namely; (1) preparation, (2) elaboration, (3) synthesis, (4) concept realization, and (5) completion. In creating the works, the author used an electric rotary tool and provided Minangkabau motifs by adding glitter powder and beads. The resulting works were 7 works with titles including: Itiak Pulang Patang (ducks coming home in the afternoon), Bada Mudiak ( anchovy upstream), Pucuak Rabuang (bamboo shoots), Kaluak Paku (rolluangan fern), Siriah Gadang (large betel), Bungo Taratai in aia (lotus flower in water), and Saik Galamai (pieces of gelamai)